Knowledge, attitudes and practice of consumers towards single-use plastics at Korle-Gonno, Ghana - Elijah Kwasi Peprah; Samuel Agyabeng Boapeah; Roberta Amewor; Christine Tettey; Forgive Awo Norvivor; Doreen Danso; Reginald Eshun; Hope Yaw Attah; Michael Affordofe (PLoS ONE, 2025)
Introduction Plastic pollution, particularly from single-use plastics (SUPs), is an increasing environmental problem, especially for coastal communities dependent on marine ecosystems for their livelihood, food, and recreation. The Korle-Gonno community in Ghana epitomizes this: inadequate waste management systems and heavy reliance on SUPs. This study aimed to explore the drivers of consumer attitudes toward SUPs to inform effective interventions. Methods A descriptive cross-sectional study was conducted among 198 residents of Korle-Gonno. The study used a multi-stage sampling method to select participants, targeting adults who had lived in the community for at least five years. Data was collected using a structured questionnaire that assessed socio-demographics, knowledge, concerns, attitudes, and practices regarding SUPs. Scores were categorized into low, moderate, and high levels, and data were analyzed using STATA 17.0. Descriptive and inferential statistics were analyzed, including chi-square tests and logistic regression. Results The study showed that 51% of the respondents have low knowledge of SUPs and although they considered SUPs as one of the major contributors to pollution, only 10.1% reported recycling plastics, while most relied on improper methods of plastic disposal. Important predictors of positive attitude towards the reduction of SUPs were: high levels of concern (aOR=2.37, 95% CI = 1.09–5.15) and good perception of environmental impact (aOR=4.59, 95% CI = 2.15–10.83). Those who had lived in the community for more than 20 years were likely to have positive attitudes (aOR=2.45, 95% CI = 1.04–5.77). Conclusion SUP pollution in Korle-Gonno is fueled by a lack of knowledge, inappropriate practices, and inadequate infrastructure. While these are major challenges, the community strongly supports regulation and corporate responsibility. Public education, improvement of the recycling system, and promotion of biodegradable alternatives are critical intervention strategies to solve this problem sustainably.